Guidelines for Selecting or Modifying Logos - Henderson, Pamela W.; Cote, Joseph A. (Journal of Marketing, 1998)
The authors develop guidelines to assist managers in selecting or modifying logos to achieve their corporate image goals. An empirical analysis of 195 logos, calibrated on 13 design characteristics, identified logos that meet high-recognition, low-investment, and high-image communication objectives. High-recognition logos (accurate recognition created by high investment) should be very natural, very harmonious, and moderately elaborate. Low-investment logos (false sense of knowing and positive affect) should be less natural and very harmonious. High image logos (professional look and strong positive image) must be moderately elaborate and natural. The authors illustrate the guidelines with real logos.